(untitled) (Bangladesh Heart Journal, 2023)
Background: ST segment elevation myocardial infarction (STEMI) is associated with ventricular dysfunction due to ischemic myocardial damage, decrease ventricular compliance and increase filling pressure resulting in left atrial stretching, dilatation, increase left atrial volume and subsequently increase secretion of atrial natriuretic peptides. This study is aimed to determine the association between increase left atrial volume index (LAVI) and in-hospital outcome and to explore the correlation between LAVI and NT-proBNP in patients suffered from acute ST segment elevation myocardial infarction (STEMI). Methods: This cross sectional analytic study include 92 patients with acute STEMI admitted for reperfusion therapy. 2D Echocardiography was done and based on LAVI, study population were grouped as Group A:LAVI >34 ml/m2 (n=48) & Group B:LAVI d”34 ml/m2(n=44). Results: In-hospital outcome, plasma level of NT-proBNP and echcardiographic evaluation was done successfully. Mean NT-proBNP was significantly high in Group A than Group B (1234.6±738.77 vs 689.52±721.04). Statistically significant association was present between LAVI and adverse in-hospital outcome. Persistent chest pain, hypotension, acute LVF, arrhythmia, acute kidney injury were higher in Group A than Group B and acute LVF occurred significantly (p<0.05) more in Group A than Group B (38.3% vs. 9.1%). Statistically significant correlation was present between LAVI and NT-proBNP (r=0.453; p=0.001). According to receiver-operating characteristic curve (ROC) analysis, LAVI with a cut off value of 33.75 ml/m2 can predict adverse in-hospital outcome in patients of acute STEMI underwent reperfusion therapy with sensitivity 66.2% and specificity 75% and better than NT-proBNP with more sensitivity (66.2% vs 50.0%). Conclusion: Significant association present between increase LAVI and adverse in-hospital outcome and it can predict adverse in-hospital outcome better than NTproBNP. There is also positive correlation between LAVI and NT-proBNP in acute STEMI. Bangladesh Heart Journal 2023; 38(1): 46-57